94.4k views
4 votes
-5c + 6 = -4 what the first step

2 Answers

5 votes

Answer:

Let's solve your equation step-by-step.

−5c+6=−4

Step 1: Subtract 6 from both sides.

−5c+6−6=−4−6

−5c=−10

Step 2: Divide both sides by -5.

−5c

−5

=

−10

−5

c=2

Explanation:

Wanna chat add me as a friend OR COME TO SANP (ADAMBELAL839)

User Chenequa
by
5.9k points
3 votes
Subtract 6 from both sides ( subtract 6 form 6 to get 0 then subtract 6 form -4 to get 2) that’s the first step
User Sean Parsons
by
6.0k points